1987
DOI: 10.1038/bjc.1987.175
|View full text |Cite
|
Sign up to set email alerts
|

Tumour-associated trypsin inhibitor (TATI) in human ovarian cyst fluid. Comparison with CA 125 and CEA

Abstract: Summary The levels of tumour-associated trypsin inhibitor (TATI), CA 125 and CEA were measured in ovarian cyst fluids from 21 patients. TATI in cyst fluid was immunologically and physicochemically similar to the peptide originally isolated from the urine of a patient with ovarian cancer. Mucinous cysts contained significantly higher levels of TATI than did serous cysts. Immunohistochemically TATI was localized in the apical parts of cells of mucinous ovarian cysts. These results suggest that this tumour-associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
22
1

Year Published

1988
1988
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 20 publications
(16 reference statements)
4
22
1
Order By: Relevance
“…In other types of ovarian cancer other mechanisms may contribute to the elevation, because high levels of TATI are only occasionally found in the cyst fluid of nonmucinous tumours (Halila et al, 1987). TATI may become elevated not only in cancer but also in connection with severe inflammatory (Huhtala et al, 1983), especially hepatobiliary, disease (Haglund et al, 1986) and postoperatively (Matsuda et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other types of ovarian cancer other mechanisms may contribute to the elevation, because high levels of TATI are only occasionally found in the cyst fluid of nonmucinous tumours (Halila et al, 1987). TATI may become elevated not only in cancer but also in connection with severe inflammatory (Huhtala et al, 1983), especially hepatobiliary, disease (Haglund et al, 1986) and postoperatively (Matsuda et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…The latter tumours regularly contain high levels of CA 125, the levels of which are lower in mucinous tumours (Halila et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, in tumour tissues, such a proteolytic enzyme and its inhibitor occur together, and the latter could be involved in the inhibition of the former enzymatic activity (Kataoka et al, 1989;Strauli et al, 1980;Turpeinen et al, 1988). Tumour-associated trypsin inhibitor, TATI, is a peptide identified in ovarian cancerous extracts, the N-terminal amino acid sequence of which is very similar to PSTI (Halila et al, 1987). The ability of TATI to inhibit not only trypsin but also some fibrinolytic enzymes, such as plasmin, urokinase, and tissue-type plasminogen activator, has been recently demonstrated in its physiological concentrations, suggesting that TATI has a possible role in proteolytic control involving these proteinases (Turpeinen et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…During patient monitoring, the serum concentrations of SPINK1 reflect the development of recurrent disease (17 ). Compared to serum concentrations, up to 1000-fold higher concentrations of SPINK1 have been found in cyst fluid from both benign and malignant ovarian cysts, but increased serum concentrations are rare in patients with benign cysts (18 ). A recent study (19 ) of mucinous borderline ovarian tumors showed that increased serum concentrations of SPINK1 were found in these patients and a significant correlation was observed with tissue expression of claudin-5.…”
Section: Ovarian Cancermentioning
confidence: 99%